Managing Innovation in an Unstable World: Challenges of Global Competition for European Innovative and Proactive Firms - Carlo Binder; Andrea Mantovani (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
Innovation and marketing strategies adopted by multinational companies in the globalized economy are subject to continuous challenges. Consider EU exporting companies that produce, for example, solar panels. Depending on political elections and the ensuing support for environmental policies (or the lack thereof), their innovative strategy may reveal either extremely successful or futile. The aim of this paper is to explore the conditions under which innovative and proactive companies survive in a global scenario that changes based not only on economic but also on political as well as social factors.
Keywords: L2; M1; O3; 330; Innovation; Strategy; Globalization